Curious George visits the zoo - Rey, Margret; Shalleck, Alan J. (Boston : Houghton Mifflin, 1985)
Curious George visits the zoo and manages to both cause trouble and make up for it in his inimitable fashion.
"Adapted from the Curious George film series."
Accelerated Reader AR
Keywords: Monkeys -- Fiction; Zoos -- Fiction